2016
DOI: 10.1186/s12890-016-0206-4
|View full text |Cite
|
Sign up to set email alerts
|

Infection biomarkers in primary care patients with acute respiratory tract infections–comparison of Procalcitonin and C-reactive protein

Abstract: BackgroundThere is a lack of studies comparing the utility of C-reactive protein (CRP) with Procalcitonin (PCT) for the management of patients with acute respiratory tract infections (ARI) in primary care. Our aim was to study the correlation between these markers and to compare their predictive accuracy in regard to clinical outcome prediction.MethodsThis is a secondary analysis using clinical and biomarker data of 458 primary care patients with pneumonic and non-pneumonic ARI. We used correlation statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Studies comparing procalcitonin and C-reactive protein have reported low correlation of these markers suggesting that important differences exist, which could lead to different recommendations on antibiotic use in individual patients. 62,63 However, head-tohead studies assessing the clinical effect of procalcitonin compared with C-reactive protein guided treatment algorithms are still needed. Finally, one strategy that has had an impact in the inpatient setting is early provider notification of procalcitonin results and this strategy might improve the performance of procalcitonin-guided treatment algorithms if used in future studies done in primary care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing procalcitonin and C-reactive protein have reported low correlation of these markers suggesting that important differences exist, which could lead to different recommendations on antibiotic use in individual patients. 62,63 However, head-tohead studies assessing the clinical effect of procalcitonin compared with C-reactive protein guided treatment algorithms are still needed. Finally, one strategy that has had an impact in the inpatient setting is early provider notification of procalcitonin results and this strategy might improve the performance of procalcitonin-guided treatment algorithms if used in future studies done in primary care settings.…”
Section: Discussionmentioning
confidence: 99%
“…We have also not discussed in detail other markers of infection such as CRP. However, there is a lack of well-done and large studies comparing the effect of both markers when used in the context of antibiotic stewardship [82, 83]. …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most studies failed to objective correlation between CRP level and severity of the sepsis [21]. Meili et al, (2016), demonstrated that CRP < 100 mg/l is signi cantly associated with worst acute respiratory tract infections but have moderate prognostic accuracy in primary care patients to predict clinical outcomes [22]. CRP help to diagnose equivocal cases of appendicitis, cholecystitis, pancreatitis and pelvic in ammatory disease but faster and more interpretable tests are available.…”
Section: Discussionmentioning
confidence: 99%